Performance Indicators - Hackett, E. Raymond; Carrigan, Sarah D. (Education Policy Analysis Archives, 1998)
Measures of overall institutional performance were explored from a decision support perspective with twenty similar Carnegie Classification Baccalaureate II institutions. The study examined the usefulness of performance indicators in campus decision making following both a hypothesis testing and case study approach. Two conclusions were reached: first, that the performance measures most commonly cited in the literature as measures of institutional financial viability are of limited use for institution specific policy development; and second, that performance indicators are most effectively used within an institution specific, whole system framework.